2016
DOI: 10.1002/lpor.201600021
|View full text |Cite
|
Sign up to set email alerts
|

Directional fluorescence emission from a compact plasmonic‐diamond hybrid nanostructure

Abstract: Ultracompact directional optical nanoantennas are rapidly gaining popularity yet still challenging tasks to construct at the nanoscale. Here, we experimentally demonstrate unidirectional emission from a fluorescent nanodiamond coupled with a single gold nanorod. Different configurations of the assembled hybrid nanostructures were realized via stepby-step atomic force microscope nanomanipulation. The emission patterns can be controlled by adjusting the configurations, i.e., the gold nanorod orientation and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…In this study, we proposed to perform in situ single particle measurements to circumvent previous experimental limitation. We combined atomic force microscope (AFM) nanomanipulation technique with single particle spectroscopy method . We directly measured and compared the scattering and PL spectra of the same single GNR before and after coupling with monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we proposed to perform in situ single particle measurements to circumvent previous experimental limitation. We combined atomic force microscope (AFM) nanomanipulation technique with single particle spectroscopy method . We directly measured and compared the scattering and PL spectra of the same single GNR before and after coupling with monolayer graphene.…”
Section: Introductionmentioning
confidence: 99%
“…Following this study, Shen et al. showed that unidirectional emission from a single FND could be generated if it was coupled with a GNR . The result was attributed to the interference between the electromagnetic fields produced by the dipole‐like source and the out‐of‐phase dipole induced in the GNR.…”
Section: Gold/diamond Nanohybridsmentioning
confidence: 81%
“…The MoS 2 was obtained by a chemical vapor deposition method. Then, the sample was investigated by the single-particle spectroscopy 40,41 . Briefly, the microspectroscopy system integrated white-light dark-field scattering, photoluminescence, and AFM.…”
Section: Resultsmentioning
confidence: 99%